Attitudes of Malaysian vocational trainee teachers towards the integration of computer in teaching - Bakar, Ab. Rahim; Mohamed, Shamsiah (Association for the Advancement of Computing in Education, 2001)
This paper is a report of a study conducted to assess the attitudes of Malaysian vocational trainee teachers towards the integration of computer in teaching. One hundred and thirty trainee teachers participated in the study of whom 12.2% was male trainees and 87.8% was female trainees. They majored in agricultural science (13.7%), home science (17.3%), economics and accounting (22.3%), others (46.7%). Their minors areas were living skills (25.5%), business studies (70.5%), and economics (4.3%). In general, vocational trainee teachers had a positive attitudes towards the integration of computers in teaching. However, the attitudes towards the integration of computers in teaching did not differ among students with different majors and minors. Majority of them planned to integrate computers in teaching. A significant correlation was observed between their attitudes towards the integration of computers and their plan to integrate computers in teaching. They believed that all trainee teachers should be required to enroll in a computer class while in teacher training.